2023
DOI: 10.3390/antiox12030628
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary (Rosmarinus officinalis L.) Glycolic Extract Protects Liver Mitochondria from Oxidative Damage and Prevents Acetaminophen-Induced Hepatotoxicity

Abstract: Rosmarinus officinalis L. (rosemary) is an aromatic culinary herb. Native to the Mediterranean region, it is currently cultivated worldwide. In addition to its use as a condiment in food preparation and in teas, rosemary has been widely employed in folk medicine and cosmetics. Several beneficial effects have been described for rosemary, including antimicrobial and antioxidant activities. Here, we investigated the mechanisms accounting for the antioxidant activity of the glycolic extract of R. officinalis (Ro) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 97 publications
1
0
0
Order By: Relevance
“…Finally, the obtained results showed that both extracts demonstrated a great antioxidant activity by reducing ROS production and modulating mitochondrial function. This effect was also recently reported by Guimarães and coworkers [68] where a rosemary extract was demonstrated to protect liver mitochondria from hepatotoxicityrelated oxidative stress [68]. These data support the hypothesis that WRO and CRO extracts impair mitochondrial activity reducing their ability to produce ROS and sustain the inflammatory process, confirming that it is possible and safer to use the cultivated rosemary plants instead of wild ones.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the obtained results showed that both extracts demonstrated a great antioxidant activity by reducing ROS production and modulating mitochondrial function. This effect was also recently reported by Guimarães and coworkers [68] where a rosemary extract was demonstrated to protect liver mitochondria from hepatotoxicityrelated oxidative stress [68]. These data support the hypothesis that WRO and CRO extracts impair mitochondrial activity reducing their ability to produce ROS and sustain the inflammatory process, confirming that it is possible and safer to use the cultivated rosemary plants instead of wild ones.…”
Section: Discussionsupporting
confidence: 87%